Closing the parachute and opening the umbrella: Strategies for inclusivity and representation in producing impactful coastal ecosystem research - Laumann, Katie May; Hoad, Nicholas M.; Alvaro, Lauren; Badri, Shahrzad Lili; Burke, Noirin; Carew, Annie; Corte, Guilherme N.; Croquer, Aldo; Shah Esmaeili, Yasmina; Farrell, Martha; Kouchi, Naoko; Lee, Juhyung; et al. (Cambridge Prisms: Coastal Futures, 2025)
Parachute science is the problematic and extractive practice of non-local researchers taking data, knowledge and information from communities of which they are not members, failing to engage the local community and local scientists, marginalizing them in most aspects of the research, and using the results to their own benefit. Perpetuated by colonialism and unequal access to resources such as funding, education and data, it is harmful to local scientists and undervalues the contributions of the community as a whole. Ultimately, it erodes trust within the scientific community and, more broadly, builds dependence on foreign researchers and makes science less global and collaborative. Increasing international and cross-cultural collaborations while being careful to avoid parachute science can help minimize these impacts. Here, we offer our perspectives on parachute science and suggestions on how to avoid it, based on our experiences conducting research internationally with diverse scientists and communities, including both academics and non-academics. Instead of a parachute, we suggest opening the scientific “umbrella” to incorporate diverse perspectives and local contributions in generating relevant and impactful scientific insight. La ciencia de paracaídas es la práctica problemática y extractiva de investigadores no locales que toman datos, conocimientos e información de comunidades de las que no son miembros, no logran involucrar a la comunidad local y a los científicos locales, los marginan en la mayoría de los aspectos de la investigación y utilizan los resultados para su propio beneficio. Perpetuado por el colonialismo y el acceso desigual a recursos como la financiación, la educación y los datos, es perjudicial para los científicos locales y subestima las contribuciones de la comunidad en su conjunto. En última instancia, erosiona la confianza dentro de la comunidad científica y, en términos más generales, genera dependencia de los investigadores extranjeros y hace que la ciencia sea menos global y colaborativa. Aumentar las colaboraciones internacionales e interculturales, al tiempo que se tiene cuidado de evitar la ciencia de paracaídas, puede ayudar a minimizar estos impactos. Aquí, ofrecemos nuestras perspectivas sobre la ciencia de paracaídas y sugerencias sobre cómo evitarlo, basándonos en nuestras experiencias realizando investigaciones a nivel internacional con diversos científicos y comunidades, incluidos académicos y no académicos. En lugar de un paracaídas, sugerimos abrir el “paraguas” científico para incorporar diversas perspectivas y contribuciones locales en la generación de conocimientos científicos relevantes e impactantes.